2022
DOI: 10.1136/bmj.o143
|View full text |Cite
|
Sign up to set email alerts
|

Long covid in children and adolescents

Abstract: Symptoms involving almost every organ system have been reported SARS-CoV-2 infection. 1 -3 Estimates of the prevalence of long covid (also called post-covid-19 condition, post-acute sequelae of covid-19, or chronic covid syndrome) vary considerably, partly because of confusion around the definition. The term long covid encompasses a broad range of symptoms, including objective complications of covid-19 (pulmonary fibrosis, myocardial dysfunction), mental health conditions, and more subjective, non-specific s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
0
4

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 15 publications
0
30
0
4
Order By: Relevance
“…We recently reported that the frequency of persistent symptoms after COVID-19 in children and adolescents is uncertain. 2 , 3 Almost all of the studies on ‘long COVID’ in this age group have considerable limitations, for example, the inclusion of children without confirmed SARS-CoV-2 infection and a lack of appropriate control groups. 3 , 4 As the number of published studies on this topic has doubled, we reassessed the current evidence on long COVID in children and adolescents.…”
mentioning
confidence: 99%
“…We recently reported that the frequency of persistent symptoms after COVID-19 in children and adolescents is uncertain. 2 , 3 Almost all of the studies on ‘long COVID’ in this age group have considerable limitations, for example, the inclusion of children without confirmed SARS-CoV-2 infection and a lack of appropriate control groups. 3 , 4 As the number of published studies on this topic has doubled, we reassessed the current evidence on long COVID in children and adolescents.…”
mentioning
confidence: 99%
“…A diferencia de lo que muchos creen, estas observaciones no intentan evitar vacunaciones, sino más bien reevaluar el tipo de vacuna administrada en adolescentes, su frecuencia, y alertar a médicos sobre los eventuales síntomas. La falta de una estrategia proactiva de dichas organizaciones dio cabida a la entrega de información a la población general a través de la prensa y otros medios de difusión, un error que desencadenó una ola de comentarios, a veces llevados al extremo, en redes sociales 53,[75][76][77][78][79][80][81] . Se ha propuesto que otro efecto beneficioso de vacunar a NNA contra COVID-19 pudiera ser la prevención síndrome de COVID-19 prolongado o síndrome de COVID-19.…”
Section: Macro-nivelunclassified
“…Con los datos disponibles, aparentemente su frecuencia es mucho más baja de lo que inicialmente se pensó, pero es un área de investigación en la actualidad. 81,84 El desconocimiento del nuevo agente infeccioso, su rapidez de propagación, extensión geográfica y gravedad, produjeron razonable e ineludiblemente un constante cambio de las propuestas de expertos y las medidas adoptadas por los gobiernos. Si bien el primer año de la pandemia era esperable la incertidumbre, la y los errores, en el segundo año las medidas impulsadas férreamente en un comienzo debieran haber sido evaluadas, modificando y enfocando las estrategias, educando a la población y asumiendo y corrigiendo las políticas desacertadas, que en el tiempo se mostraron fútiles.…”
Section: Macro-nivelunclassified
“…A nationwide registry study from Norway finds a substantial short term increase in children’s use of primary care in the first month after a positive SARS-CoV-2 test result without, importantly, an effect on hospital services (doi:10.1136/bmj-2021-066809; doi:10.1136/bmj.o143). 1213 Workload pressures in primary care raise the question: how many GPs is enough? John Appleby explains why it is a hard question to answer (doi:10.1136/bmj.o123).…”
mentioning
confidence: 99%